STRATEGI PERKEMBANGAN INDUSTRI MIKRO PADA USAHA BAKSO HAJI DUL DI KOTA PONTIANAK - Saktiawan, Ade Rizki; Asriati, Nuraini; Warneri, Warneri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research is research related to the development strategy oflthe micro industry in the Bakso Haji Dul business in Pontianak City. The aim of this research is to find out what strategies and obstacles influence the development process and running of the business, as well as find out the income figures for 2020-2022 in the Bakso Haji Dul micro industry. The author uses a qualitative research method with a descriptive approach model. Data collection techniques were carried out through observation, interviews and documentation involving the author with 2 informants, namely the business owner and employees in the Bakso Haji Dul production section. The research results show that the development strategy used is adding product variants, creating a business logo, implementing the latest sales concept and improving service quality. During the Covid-19 pandemic, the owner of2the Bakso Haji Dul business attempted to produce innovations and creative ideas which continued to be developed through the emergence of the newest products. This is what causes income figures to continue to increase every year. Bakso Haji Dul's business income in 2020 and 2021 increased by 64.78%, while in 2021 and 2022 it was 64.78%. Then followed in 2021 to 2022 there was an increase of 79.25%. Through this stage of development, the Bakso Haji Dul business often experiences obstacles in the form of pressure from business competition conditions and soaring raw material prices which result in business owners having to organize plans to avoid losses.